PENGARUH ORIENTASI BISNIS DAN KEPUASAN BISNIS TERHADAP KOMITMEN ORGANISASIONAL DAN DAMPAKNYA TERHADAP KINERJA BISNIS IBO - HANNA M. DAMANIK; MARTIN LUTER PURBA; HENDRIK E.S. SAMOSIR (JURNAL ILMIAH MAKSITEK, 2020)
Oriflame is one of company that uses MLM (Multi Level Marketing) strategies in marketing its products. The model used by this company is the IBO (Independent Business Owner) where in this way the company gives freedom to agents independently to be able to compete in the marketplace. Oriflame needs IBOs who are committed to building their business network because IBOs have a very high role in achieving the goals of Oriflame. Business orientation and business satisfaction will cause IBO commit to the business runs. There were 52 IBOs who were respondents in this study with a minimum level of 9% in February 2020. This study used a variance-based or component-based approach with PLS analysis orientation. Based on this research, it can be concluded that the results of this study indicate that business satisfaction has a positive effect on organizational commitment with a coefficient value of 0.860, business orientation has a positive effect on organizational commitment with a coefficient value of 0.092, organizational commitment has a positive effect on IBO business performance with a value coefficient 0.918.